A Berberine Bridge Enzyme-Like Protein, GmBBE-like43, Confers Soybean's Coordinated Adaptation to Aluminum Toxicity and Phosphorus Deficiency - Chen, Qianqian; Li, Jifu; Liu, Guoxuan; Lu, Xing; Chen, Kang; Tian, Jiang; Liang, Cuiyue (Frontiers in Plant Science, 2022)
Phosphorus (P) deficiency and aluminum (Al) toxicity are often coexist and are two major limiting factors for crop production in acid soils. Pectin demethyl-esterification due to Al toxicity and P deficiency increase the possibility for active de-methylated oligogalacturonides (OGs) production. Therefore, the purpose of this study was to clarify the mechanism of controlling OGs homeostasis under Al and low P stresses through functional characterization of GmBBE-like43, a berberine bridge enzyme-like protein encoding gene. The present qRT-PCR assays confirmed the Pi-starvation and Al-stress up-regulated expression pattern of GmBBE-like43 in soybean (Glycine max) roots, while expression of a GmBBE-like43-GFP chimera in both tobacco leaf and common bean hairy roots demonstrated its cell wall localization. Both transgenic Arabidopsis and soybean hairy roots revealed the function of GmBBE-like43 in promoting root growth under both Al and low P stresses. Moreover, GmBBE-like43-overexpression resulted in more H2O2 production on the soybean hairy root surface with oligogalacturonides (OGs) application and antagonize the effects of Al on the expression of two SAUR-like genes. Taken together, our results suggest that GmBBE-like43 might involve in soybean coordinate adaptation to Al toxicity and Pi starvation through modulation of OGs-oxidation in cell wall.